Developing Student’s Speaking Skill Based On Aivideo at Senior High School Grade X SMK Yayasan Taruna Bangsa Sawit Seberang 2024/2025 - Febriana, Dwi Intan; Risnawaty; Asnawi (International Journal of Educational Research Excellence, 2026)
This study aims to produce AI-based learning video media that can be used to improve the speaking skills of tenth-grade students at SMK Yayasan Taruna Bangsa Sawit Seberang. This research is a research and development (R&D)study using the ADDIE model, which consists of five stages. The trial subjects included media experts, material experts, and learning experts. The object of the study was the developed AI-based learning video. Data collection was conducted through a validation questionnaire administered to the expert validators. The results showed that the learning media received a validity score of 83 from the media experts, 94 from the material experts, and 92 from the learning experts, all of which fall into the "Very Valid" category. Furthermore, the percentage of students' speaking skills increased from 37.14% before using the AI video to 82.85% after the implementation of the AI video. Therefore, it can be concluded that the developed AI-based learning video is highly valid and effective in improving the speaking skills of tenth-grade vocational school students